2015
DOI: 10.1186/s12967-015-0614-x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effect of the proton pump inhibitor esomeprazole leading to suppression of lung inflammation and fibrosis

Abstract: BackgroundThe beneficial outcome associated with the use of proton pump inhibitors (PPIs) in idiopathic pulmonary fibrosis (IPF) has been reported in retrospective studies. To date, no prospective study has been conducted to confirm these outcomes. In addition, the potential mechanism by which PPIs improve measures of lung function and/or transplant-free survival in IPF has not been elucidated.MethodsHere, we used biochemical, cell biological and preclinical studies to evaluate regulation of markers associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 90 publications
1
130
0
1
Order By: Relevance
“…Our preclinical in vivo study revealed that oral esomeprazole mitigates inflammatory and fibrotic responses (about 50% reduction of each parameter) in a rodent model of bleomycin-induced lung injury (47). Overall, the reported data from in vitro and in vivo studies demonstrating the beneficial role of PPIs on processes involved in lung inflammation and fibrogenesis suggest that PPIs, in contrast to antireflux surgery, may exert favorable effects in measures of lung function and survival in IPF through biological regulation of inflammatory and fibrotic processes rather than suppression of gastric reflux or microaspiration (Figure 3).…”
Section: Ppis and Their Emerging Antiinflammatory-antifibrotic Rolementioning
confidence: 82%
See 1 more Smart Citation
“…Our preclinical in vivo study revealed that oral esomeprazole mitigates inflammatory and fibrotic responses (about 50% reduction of each parameter) in a rodent model of bleomycin-induced lung injury (47). Overall, the reported data from in vitro and in vivo studies demonstrating the beneficial role of PPIs on processes involved in lung inflammation and fibrogenesis suggest that PPIs, in contrast to antireflux surgery, may exert favorable effects in measures of lung function and survival in IPF through biological regulation of inflammatory and fibrotic processes rather than suppression of gastric reflux or microaspiration (Figure 3).…”
Section: Ppis and Their Emerging Antiinflammatory-antifibrotic Rolementioning
confidence: 82%
“…Our recent mechanistic study demonstrated that an archetype PPI, esomeprazole, possesses a pleiotropic salutary effect in regulating processes involved in the development and progression of lung inflammation and fibrosis (47). We demonstrated this effect of esomeprazole using in vitro studies of primary lung fibroblasts, endothelial and epithelial cells exposed to bleomycin or ionizing radiation.…”
Section: Ppis and Their Emerging Antiinflammatory-antifibrotic Rolementioning
confidence: 93%
“…[106] Esomeprazole has been observed to be antiinflammatory, anti-oxidant and anti-apoptotic via directly down-regulating ROS, upregulating the anti-oxidants nuclear factor 2-related factor-2 (Nrf 2 ) and heme oxygenase-I (HO-I). [107] In conclusion, case report points esomeprazole out as a drug that may contribute to a favourable forecast in the pre-eclampsia syndrome and safely attenuate the major ultrasonic and biochemical indices of pre-eclampsia. Appropriate national and international trials would delineate its place not only in the treatment but also in the prevention of pre-eclampsia and intra-uterine growth restriction (IUGR).…”
mentioning
confidence: 86%
“…However, esomeprazole is also found to control Inflammation, by suppressing the expression of pro-inflammatory molecules and vascular cell molecule-1, inducible nitric oxide synthase, tumor necrosis factor-alpha (TNF-α) and interleukins (IL-1β and IL-6) in cell culture studies. This function was identified, based on strong induction of the stress-inducible cytoprotective protein heme oxygenase-1 (HO1), and the anti-fibrotic effect is associated with potent inhibition of fibroblast proliferation, as well as downregulation of profibrotic proteins including receptors for transforming growth factor β (TGFβ), fibronectin and matrix metalloproteinases (MMPs) 14 .…”
Section: Methodsmentioning
confidence: 99%